Role of FtsH2 in the repair of Photosystem II in mutants of the cyanobacterium Synechocystis PCC 6803 with impaired assembly or stability of the CaMn(4) cluster - Komenda, Josef; Knoppová, Jana; Krynická, Vendula; Nixon, Peter J; Tichý, Martin (Biochimica et biophysica acta, 2010)
The FtsH2 protease, encoded by the slr0228 gene, plays a key role in the selective degradation of photodamaged D1 protein during the repair of Photosystem II (PSII) in the cyanobacterium Synechocystis sp. PCC 6803. To test whether additional proteases might be involved in D1 degradation during high rates of photodamage, we have studied the synthesis and degradation of the D1 protein in DeltaPsbO and DeltaPsbV mutants, in which the CaMn(4) cluster catalyzing oxygen evolution is less stable, and in the D1 processing mutants, D1-S345P and DeltaCtpA, which are unable to assemble a functional cluster. All four mutants exhibited a dramatically increased rate of D1 degradation in high light compared to the wild-type. Additional inactivation of the ftsH2 gene slowed the rate of D1 degradation dramatically and increased the level of PSII complexes. We conclude that FtsH2 plays a major role in the degradation of both precursor and mature forms of D1 following donor-side photoinhibition. However, this conclusion concerned only D1 assembled into larger complexes containing at least D2 and CP47. In the DeltapsbEFLJ deletion mutant blocked at an early stage in PSII assembly, unassembled D1 protein was efficiently degraded in the absence of FtsH2 pointing to the involvement of other protease(s). Significantly, the DeltaPsbO mutant displayed unusually low levels of cellular chlorophyll at extremely low-light intensities. The possibilities that PSII repair may limit the availability of chlorophyll for the biogenesis of other chlorophyll-binding proteins and that PsbO might have a regulatory role in PSII repair are discussed.
Keywords: mangan; messenger RNA; Peptide Hydrolases; fotosystém II (proteinový komplex); proteasy; Photosystem II Protein Complex; vápník; Thylakoids; RNA, Bacterial; mutace; Manganese; Oxidation-Reduction; polymerázová řetězová reakce s reverzní transkripcí; Calcium; bakteriální RNA; Mutation; RNA, Messenger; Reverse Transcriptase Polymerase Chain Reaction; oxidace-redukce; Synechocystis; tylakoidy